Is crossed laterality associated with academic achievement and intelligence? A systematic review and meta-analysis. - Marta Ferrero; Gillian West; Miguel A Vadillo (PLoS ONE)
Over the last century, sporadic research has suggested that people whose hand, eye, foot, or ear dominances are not consistently right- or left-sided are at special risk of suffering academic difficulties. This phenomenon is known as crossed laterality. Although the bulk of this research dates from 1960's and 1970's, crossed laterality is becoming increasingly popular in the area of school education, driving the creation of several interventions aimed at restoring or consolidating lateral dominance. However, the available evidence is fragmentary. To determine the impact of crossed laterality on academic achievement and intelligence, we conducted a systematic review and meta-analysis of articles published since 1900. The inclusion criteria for the review required that studies used one or more lateral preference tasks for at least two specific parts of the body; they included a valid measure of crossed laterality; they measured the impact of crossed laterality on academic achievement or intelligence; and they included participants between 3 and 17 years old. The final sample included 26 articles that covered a total population of 3578 children aged 5 to 12. Taken collectively, the results of these studies do not support the claim that there is a reliable association between crossed laterality and either academic achievement or intelligence. Along with this, we detected important shortcomings in the literature, such as considerable heterogeneity among the variables used to measure laterality and among the tasks utilized to measure the outcomes. The educational implications of these results are discussed.